Comments on the review by Kathrin Tiewa - Amidu, Assibi A. (Afrikanistik online, 2010)
The review of the book Matrix nominal Phrases in Kiswahili Bantu (2009), Rüdiger Köppe Verlag, in Afrikanistik online is lucid and welcome. We appreciate it very much. There are, however, a few inexactitudes that need to be corrected.
Keywords: Amidu; Bantu; Kiswahili; Nominal Phrases; Tiewa